ANALISIS LAYANAN PENINGKATAN KUALITAS HIDUP ORANG DENGAN GANGGUAN JIWA (ODGJ) - Bambang Suko Winarno (Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
There are many service models with various types of programs to improve the quality of life for mental patients. Rehabilitation centers already exist in various Indonesian cities with their social workers trying to implement therapy programs for healing and improving the quality of life for ODGJ patients. Therefore, the researcher wants to analyze in more detail what service programs are provided by social workers in rehabilitation places which will later be used as a reference material for social workers, the general public, counselors, psychologists, and academics. The method used by researchers is to use a library research method or approach (library research) or literature study where the researcher collects library data, then reads and studies to find research material. Research result. The results showed that ODGJ rehabilitation services were vocational, recreational therapy, occupational therapy, and ruqyah therapy.Keywords:Â Â quality of life; service improvement; patients with mental illness